2015
DOI: 10.1002/ange.201507418
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Studies of the Karlotoxin Class Using NMR Spectroscopy and DP4 Chemical‐Shift Analysis: Insights into their Mechanism of Action

Abstract: In bloom:Harmful algal bloom toxins derived from the dinoflagellate Karlodinium sp. produce an interesting suite of complex polyketides whichhave been shown to have hemolytic,cytotoxic and ichthyotoxic activity.Better understanding the mechanism of action for this class of compounds could lead to the development of new agents for targeting cancer-cell membranes. Ready,Set, Go! Herein, we found in aset of p-conjugated phenylaza[18]crown-6-1,2,3-triazol-fluoroionophores, which possess in ortho positionoft he ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Computational approaches, in conjunction with spectroscopic methods, provide a powerful and emerging method for the assignment of atom connectivity, relative configuration, and absolute configuration of complex molecules. , Highly noteworthy is the protocol developed recently by Martin and Williamson et al incorporating anisotropic NMR parameters with computational approaches to determine the structures of complex natural products. The successful characterization of karlotoxin 2 (KmTx2) followed by KmTx8 and KmTx9 was supported by NMR chemical shift calculation tools including gauge-including atomic orbitals (GIAO) and DP4+ probability studies in conjunction with heteronuclear single quantum coherence (HSQC) spectroscopy studies. Excited-state time-dependent density functional theory (TDDFT) calculations were applied here in conjunction with experimental electronic circular dichroism (ECD) spectroscopy to determine the absolute configurations of the natural products. We also used comparison of experimental and calculated 1 H and 13 C NMR chemical shifts of different regioisomers matching the chemical formula of aleutianamine to help verify that the structure was correctly assigned. The protocol presented here involves orchestration of a number of computational methods in combination with spectroscopic analyses, leading to the discovery and establishment of the well-defined structure for aleutianamine.…”
Section: Introductionmentioning
confidence: 99%
“…Computational approaches, in conjunction with spectroscopic methods, provide a powerful and emerging method for the assignment of atom connectivity, relative configuration, and absolute configuration of complex molecules. , Highly noteworthy is the protocol developed recently by Martin and Williamson et al incorporating anisotropic NMR parameters with computational approaches to determine the structures of complex natural products. The successful characterization of karlotoxin 2 (KmTx2) followed by KmTx8 and KmTx9 was supported by NMR chemical shift calculation tools including gauge-including atomic orbitals (GIAO) and DP4+ probability studies in conjunction with heteronuclear single quantum coherence (HSQC) spectroscopy studies. Excited-state time-dependent density functional theory (TDDFT) calculations were applied here in conjunction with experimental electronic circular dichroism (ECD) spectroscopy to determine the absolute configurations of the natural products. We also used comparison of experimental and calculated 1 H and 13 C NMR chemical shifts of different regioisomers matching the chemical formula of aleutianamine to help verify that the structure was correctly assigned. The protocol presented here involves orchestration of a number of computational methods in combination with spectroscopic analyses, leading to the discovery and establishment of the well-defined structure for aleutianamine.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis has represented a leap forward in the practice of elucidating structures. It has assisted in the analyses of data sets belonging to bulky molecules and even revision of some wrongly assigned structures. , To further validate the results after optical rotation and NMR chemical shift calculations, we fed the experimental and computed data sets of NMR into the DP4 applet by Goodman et al, and the results of DP4 analysis showed that our interpretation of the NMR data and the optical rotation calculation was correct. The DP4 analysis results have been presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The karlotoxin family stands out as a unique and well-studied group of fish-killing toxins. Their modes of action have been proposed (Waters et al, 2015), providing a foundation for understanding the putative toxins we identified in this study. This apparent connection with the karlotoxin family not only expands our understanding of leadbeaterins, but also provides a valuable reference point for further investigations into their biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in characterization of the chemical structures of the toxins of Karlodinium parvum (karlotoxins), Prymnesium parvum (prymnesins), and Karenia brevisulcata (brevisulcenals), the exact mechanisms by which these microalgae cause finfish mortality are not yet fully elucidated (Manning and La Claire, 2010; Van Wagoner et al, 2010; Deeds et al, 2015; Rasmussen et al, 2016; Binzer et al, 2019). However, the fact that the mode of action of karlotoxins has been suggested to be related to the disruption of the gill cell membrane by specific binding to, for instance, cholesterol, supports that they facilitate creation of pores in the membrane (Waters et al, 2015).…”
Section: Introductionmentioning
confidence: 99%